Sustainable Agriculture through Precision Modeling and Decision Support - Bana, R. S.; Kaur, Ramanjit; Ali, Sk Asraful; Meena, Dileep; Meena, S. L.; Singh, Teekam (Chronicle of Bioresource Management, 2024)
This paper offers a comprehensive overview of cropping system models, highlighting their scope, applications, and future potential in agricultural research and decision-making. Models such as APSIM, DSSAT, STICS, InfoCrop, and EPIC are discussed, each with distinct features that cater to various agricultural needs. These models are essential for researchers, agronomists, and policymakers, providing critical insights into the complexities of cropping systems and informing sustainable agriculture strategies. Looking forward, cropping system models are poised to address significant challenges like climate change adaptation, sustainable intensification, and food security. As technological advancements continue, these models will integrate scientific knowledge with stakeholder engagement to enhance agricultural practices. To fully realize their potential, it is crucial to invest in research, capacity building, and technology transfer. Collaborative efforts across disciplines and regions will be vital in leveraging modeling tools to tackle the intricate challenges in agriculture and foster a resilient and equitable food system for the future.